(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Based on well-preserved specimens, and strictly considering the influence of extramorphological (substrate-related) factors, the use of modern techniques (computer drawings, 3D acquisitions), permitted a reliable study on footprints smaller than 20 mm. Footprints of this size were mostly considered as too small and being affected by a lot of deformation, thus preventing a substantiated analysis. Our case study focuses on the Erpetopus/Camunipes dualism. Ichnologists disagree on the value of a separation of these ichnogenera, and their discussion appears rather "philosophical" than being conducted by an accurate analysis and objective data. We restudied the holotype of Camunipes cassinisi (sp. MBS 319), together with a new specimen from Southern Alps (sp. MBG 12465) that shows five well-preserved long trackways, and compared them to selected material, including the Erpetopus willistoni holotype (sp. UGKU C-8). Results suggest a synonymy of Camunipes with Erpetopus and the new combination Erpetopus cassinisi which is distinct from E. willistoni by the following anatomical features: the pes of E. cassinisi shows higher divarication angles between digits IV-V (>50°) and I-V (>130°) and a longer and variably oriented digit V, which is long about as digit II. This has interesting paleobiogeographical consequences: E. cassinisi was probably a local ichnospecies of Erpetopus in the Southern Alps.